Addition of Natural Lime in Incinerated Sewage Sludge Ash Concrete - Tan, Yeong Yu; Doh, Shu Ing; Chin, Siew Choo (Taylor& Francis Group, 2016)
The reason of carrying out this investigation was to study the ISSA concrete after adding eggshell powder to it. In this study, four different percentages of eggshell powder with respect to cement were added into the concrete mix of Grade 30. The percentage of the ISSA was fixed at 10% as the partial cement replacement with incinerated at 800ºC. The materials used were Ordinary Portland Cement, coarse aggregates, fine aggregates, ISSA and eggshell pow-der. Based on the investigation, all the slump test results of eggshell ISSA concrete were at the desired range of worka-bility from 65-80 mm. Eggshell concrete with 15% achieve the highest compressive strength at 38.96 MPa with was 21% higher than the normal plain concrete. Moreover, addition of ISSA and eggshell powder had shown a significant reduc-tion of the rate of water absorption. Although the trend of the compressive strength decreased when the addition of egg-shell powder increased up to 20%, the compressive strength of the specimens still able to be used as structural compo-nents.